Systematic Structural Determinants of the Effects of Tetraphosphonates on Gypsum Crystallization - Akyol, Emel; Oner, Mualla; Barouda, Eleni; Demadis, Konstantinos D. (AMER CHEMICAL SOC, 2009)
In this study, the effect of phosphonate additives oil the crystallization of calcium sulfite dihydrate (CaSO4 center dot 2H(2)O, gypsum) has been investigated in aqueous solutions. Ethylenediamine-tetrakis(methylenephosphonic acid) (EDTMP), hexamethylenediamine-tetrakis(methylenephosphonic acid) (HDTMP), octamethylenediamine-tetrakis-(methylenephosphonic acid) (ODTMP), and dodecamethylenediamine-tetrakis(methylenephosphonic acid) (DDTMP) have been used as additives. It Was found that they are very effective retardants for the crystallization of calcium sulfate dihydrate. The inhibition efficiency is directly proportional to the number of methylene groups in the organic chain that connects the amino-bis-(methylenephosphonate) moieties. The degree of inhibition of crystallization was measured as an increase in induction time and reduction in crystallization rate. Particle size and crystal morphology were determined with a particle-sizer and scanning electron microscopy. According to experimental results, phosphonate additives tested in this study are very effective retardants for the formation of calcium sulfate dihydrate scale. The crystal structure of [Ca(EDTMP)(H2O)(2)]center dot H2O is also reported. This is a one-dimensional coordination polymer in which EDTMP acts as both a bidentate chelate and a bridge for Ca2+ centers.
Keywords: CALCIUM-SULFATE DIHYDRATE; SPONTANEOUS PRECIPITATION; GROWTH-INHIBITORS; SCALE INHIBITORS; AQUEOUS-SOLUTION; CRYSTAL-GROWTH; SEEDED GROWTH; CHEMISTRY; ACID; POLYELECTROLYTES; Crystallography; Materials Science